Mechanisms and Factors Influencing Resorption of Herniated Part of Lumbar Disc Herniation: Comprehensive Review - Lai Q; Gong G; Lu Y; You P; Zhu Y; Wang Z; Lin S; Jiang H; Li X; Liu J (Journal of Inflammation Research)
Qilong Lai,* Guanyi Gong,* Yukai Lu, Peijie You, Yicheng Zhu, Zhiqiang Wang, Shun Lin, Hong Jiang, Xiaochun Li, Jintao Liu Department of Orthopedic Surgery, Suzhou TCM Hospital Affiliated to Nanjing University of Chinese Medicine, Suzhou, 215009, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jintao Liu; Xiaochun Li, Department of Orthopedic Surgery, Suzhou TCM Hospital Affiliated to Nanjing University of Chinese Medicine, No. 18 Yangsu Road, Canglang New Town, Suzhou, 215009, People’s Republic of China, Email okdoctor@163.com; 13303569185@qq.comAbstract: This review systematically examines the mechanisms underlying the spontaneous resorption of lumbar disc herniation (LDH), focusing on vascularization, autophagy, apoptosis, macrophage activity, and the therapeutic potential of traditional Chinese medicine (TCM). We emphasize that resorption is influenced by factors such as herniation type, disease duration, and imaging biomarkers (eg, the bull’s-eye sign). Additionally, this review summarizes recent progress in the study of resorption mechanisms following lumbar disc herniation, providing a reference for future clinical research.Methods: Literature was systematically searched in PubMed, Web of Science, and CNKI (2000-2024) using keywords: ‘lumbar disc herniation,’ ‘resorption,’ ‘autophagy,’ ‘TCM.’ Inclusion criteria: (1) human/animal studies; (2) MRI-confirmed LDH; (3) English/Chinese full texts. Exclusion criteria: case reports (n< 10).Keywords: lumbar disc herniation, spontaneous resorption, autophagy, apoptosis, macrophage polarization, traditional Chinese medicine